ANALISA KEKERASAN MATA PISAU BAHAN ST 60 PADA MESIN PEMOTONG ZINCALUME DENGAN PROSES PERLAKUAN PANAS (HEAT TREATMENT) - Julianto, Eko; Ramadhan, Rahmad; Irawan, Doddy; Sarwono, Eko (Suara Teknik : Jurnal Ilmiah, 2019)
incalume cutting machine is the right machine to accelerate a production in a cutting system by using the main tool of an electric motor. In this study testing of the blades for cutting zincalume, in this test heat treatment (Heat Treatment) is done by cooling used oil to find out the hardness of the blade. Subsequent testing includes, among others: Hardness Testing, Microstructure and Composition to determine the comparison of violence. The analysis technique used is descriptive analysis that describes the data obtained, then explained in the form of sentences and simple graphs that are easily understood by the reader. From the results of the test, get a comparison of the hardness of the St 60 blade before the Heat Treatment and after the Heat Treatment is 10 kgf.